2016
DOI: 10.1097/paf.0000000000000225
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine-Induced Rhabdomyolysis

Abstract: Colchicine is derived from Colchicum autumnale and Gloriosa superba and is used to treat acute gout and familial Mediterranean fever (FMF). Musculoskeletal adverse effects range from myopathy to rhabdomyolysis. An 18-year-old woman, with a 2-year history of FMF treated with colchicine, took 9 colchicine pills (4.5 mg) to relieve severe abdominal pain. On the sixth day of hospitalization, the patient's condition worsened, and she died. As this was a case of fatal poisoning, a forensic autopsy was performed, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Therefore, assessing indicators of muscle damage such as creatinine kinase, myoglobin, and lactic acid dehydrogenase is recommended. [8] In our patient, these markers were not monitored at 0, 12, 24 and 36 hours in intensive care.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, assessing indicators of muscle damage such as creatinine kinase, myoglobin, and lactic acid dehydrogenase is recommended. [8] In our patient, these markers were not monitored at 0, 12, 24 and 36 hours in intensive care.…”
Section: Discussionmentioning
confidence: 74%
“…This can be considered a possible cause of azotemia in four of our patients who had CPK of more than 1,000 mg/dl and higher mortality. Arslan et al reported a case of colchicine poisoning with evidence of myocytolysis in autopsy ( 25 ) confirming the possible effect of the drug on myocytes. Colchicine has been known to induce myopathy in several other studies, as well ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 91%
“…macrolides, has taken place. [44] Feared complications included anemia, neutropenia, rhabdomyolysis [45] as well as neuromyopathy. [46] Overdoses can be potentially lethal.…”
Section: Introductionmentioning
confidence: 99%